The Management of Glucocorticoid Therapy in Liver Failure - Xue, Ran; Meng, Qinghua (Frontiers in Immunology, 2019)
Liver failure is characterized by rapid progression and high mortality. Excessive systemic inflammation is considered as the trigger of liver failure. Glucocorticoids (GCs) can rapidly suppress excessive inflammatory reactions and immune response. GCs have been applied in the treatment of liver failure since the 1970s. However, until now, the use of GCs in the treatment of liver failure has been somewhat unclear and controversial. New research regarding the molecular mechanisms of GCs may explain the controversial actions of GCs in liver failure. More results should be confirmed in a larger randomized clinical trial; this can aid the discovery of better definitions in terms of treatment schedules according to different clinical settings. Meanwhile, the timing and dosing of GCs in the treatment of liver failure should also be explored.